2021
DOI: 10.1093/nar/gkaa1218
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of the EVE-HNH endonuclease VcaM4I in the presence and absence of DNA

Abstract: Many modification-dependent restriction endonucleases (MDREs) are fusions of a PUA superfamily modification sensor domain and a nuclease catalytic domain. EVE domains belong to the PUA superfamily, and are present in MDREs in combination with HNH nuclease domains. Here, we present a biochemical characterization of the EVE-HNH endonuclease VcaM4I and crystal structures of the protein alone, with EVE domain bound to either 5mC modified dsDNA or to 5mC/5hmC containing ssDNA. The EVE domain is moderately specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…All of these SRA domain-containing endonucleases cleave DNA at a certain distance away from the modified cytosine ( 10 ). In addition, SRA domains belong to the PUA superfamily that includes other modified DNA/RNA-binding domains, such as EVE domains and YTH domains ( 2 , 12 , 13 ). These domains can also be fused to endonucleases, and most of the fusion proteins function as cytosine-modification-specific endonucleases ( 2 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these SRA domain-containing endonucleases cleave DNA at a certain distance away from the modified cytosine ( 10 ). In addition, SRA domains belong to the PUA superfamily that includes other modified DNA/RNA-binding domains, such as EVE domains and YTH domains ( 2 , 12 , 13 ). These domains can also be fused to endonucleases, and most of the fusion proteins function as cytosine-modification-specific endonucleases ( 2 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SRA domains belong to the PUA superfamily that includes other modified DNA/RNA-binding domains, such as EVE domains and YTH domains ( 2 , 12 , 13 ). These domains can also be fused to endonucleases, and most of the fusion proteins function as cytosine-modification-specific endonucleases ( 2 , 12 ). Compared to the characterized cytosine modification-dependent endonucleases, very few m6A-dependent restriction endonucleases have been identified, and DpnI is the best-known example ( 2 , 14 to 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the PCR products contain 5mC and 5hmC in many different contexts, this result suggests that the enzyme has no activity against methylated or hydroxymethylated DNA, despite the presence of the PUA (SRA-like) domain. This was surprising because it had been shown previously that PUA superfamily REases VcaM4I, SRA-like domain-containing endonuclease TagI, and PvuRts1I restricted DNA containing modified cytosines (Janosi et al, 1994;Pastor et al, 2021). Possible activity against WT T4 [glucosylated(g)-5hmC] modified DNAs remains to be tested.…”
Section: Pua-wh-hnh Fusion Endonuclease Hhiv4imentioning
confidence: 99%
“…How the modification sensor domain keeps the activity of the nuclease domain in check is not well understood. However, in some cases it can be shown that the linker has an inhibitory role for the endonuclease that is only relieved once modified DNA is bound to the reader domain and the complex reorganizes structurally (19). The PUA-wH-HNH (phi.HhiV4I) and wH-GIY-YIG (Ahi29725I and Apa233I) that were tested by run-off sequencing are consistent with this expectation.…”
Section: Cooperation With Endonuclease Domainsmentioning
confidence: 99%
“…PUA superfamily sensors comprise SRA domains with specificity for 5mC, as in MspJI (14), and related domains (15,16), originally also termed SRA domains, with specificity for 5-hydroxymethylcytosine (5hmC) and glucosyl-5-hydroxymethylcytosine (g5hmC), as in the PvuRts1I family of restriction endonucleases (17,18). The PUA superfamily also comprises EVE domains specific for 5mC and 5hmC, as found in VcaM4I (19), and YTH domains (Yth-McrB fusion) specific for 6-methyladenine (6mA) (20)(21)(22), as well as ASCH domains. Bioinformatic analysis has suggested that ASCH domains might be 6mA readers (23), but this prediction is not confirmed by experimental data so far.…”
Section: Introductionmentioning
confidence: 99%